Untangling False Assumptions Regarding Atheism and Health - Morgan, Jonathan (Zygon, 2013)
In the past decade, the cognitive science of religion has worked to find an evolutionary explanation for supernatural belief. The explanations are convincing, but have created the stereotype that atheism is unnatural. In a similar way studies linking religious belief and health have vilified atheism as unhealthy. But belief is too complex, health is too nuanced, and the data are too varied to draw such a generalization. Catherine Caldwell-Harris has developed a psychological profile to understand nonbelief as an expected outcome of individual difference and therefore natural. In a similar manner I argue that we should study the relationship between belief and health through the lens of individual differences. This approach is especially promising given recent research which indicates personality fully accounts for the relationship with well-being previously attributed to belief. This approach has the added benefit of neutralizing the conversation by understanding atheism as the healthy expression of a natural personality.